Analysis of Knowledge and Prevention Efforts to Cervical Cancer in Adolescents - Hidayati, Sri (International Conference on Sustainable Health Promotion, 2018)
The problem namely the high rate of infection in women’s reproductive organs is cervical cancer. Based on WHO data in 2015 globally found the incidence rate of cancer as many as 14.1 million cases, about 8.2 million deaths due to disease and 32.6 million cancer survivors or cancer patients have been diagnosed in the past five years, and 87% of cases occur in developing countries. In Indonesia, cervical cancer is estimated to occur in around 40 new cases per day, and 50% of them die of the disease. The purpose of this study is to determine the relationship between knowledge and efforts to prevent cervical cancer in adolescents. This research is an observational analytic study and uses the Cross-Sectional Study approach, and the population in this study were all students of Sunan Ampel Surabaya State Islamic University in July 2018 and obtained a sample of 73 samples. the results of the bivariate analysis test obtained significant results with a p-value of 0.017 (p-value <0.05) which means there is a relationship between the level of knowledge of adolescents and efforts to prevent adolescents from cervical cancer